Treatment Outcome of West Syndrome with Low-Dose ACTH Therapy in A Tertiary Care Center in Bangladesh - Das, Dhananjoy; Hasan Reza, Fahim; Ahmed, Rehena; Akther, Wahida; A Chowdhury, Mahmood (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Corticosteroids, Adrenocorticotrophic Hormone (ACTH) and vigabatrin are considered to be the first-line drug for the treatment of West Syndrome (WS). There are little consensus regarding the definitive dose, efficacy or duration of treatment of these agents in comparison to each other. So this study aimed to assess the effectiveness of low-dose ACTH in the treatment of WS. Materials and methods: A prospective observational study was conducted in the Department of Child neurology of Chattagram Maa Shishu-O-General Hospital from January 2021 to December 2022. One hundered and five children with WS aged two months to two years old enrolled in the study population. Treatment was initiated with low dose ACTH (20IU-40IU/day) and clinical and Electroencephalographic (EEG) responses were assessed at two and four weeks. Results: The mean ±SD age of the patients was 11.21 ± 7.86 months and 74.28% were male. The mean ±SD age of onset of epileptic spasm and time interval between the onset of the epileptic spasm and initiating ACTH therapy was at 6.00 ± 5.01 and 5.26 ± 4.36 months, respectively. Symptomatic epileptic spasm 76(72%) was the major category of spasm. Clinical cessation of epileptic spasm was found in 55(52.38%) and 71(67.61%) patients at two and four weeks follow-up, respectively. Cessation of hypsarrythmia in EEG was noticed in 24(27%) and 66(62.8%) patients at two and four weeks, respectively. Majority (65.71%) of the patients did not have any adverse effect. Irritability, sleep disturbance, infection and hypertension was found in 21(20%), 7(6.6%), 5(4.7%) and 3(2.8%) patients. Relapse after four weeks was found in 12 (11.4%). Conclusion: Low dose ACTH was effective in cessation of spasm and resolution of hypsarrhythmia in with children WS. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 87-90